Functional and nutritional characterization of a natural diet based on BIO102 iron biofortified beans in newly weaned mice - Jiménez‐Cardozo, N.; Díaz‐Vesga, Magda C.; Gallego-Castillo, Sonia; Álvarez, Daniel; Orozco‐Agredo, Juan Camilo; Ortega, José Guillermo; Morales‐Jiménez, Camilo (Wiley, 2024)
Childhood malnutrition persists as a critical issue in Latin America, particularly affecting protein and iron intake among children. Biofortification, enhancing crop nutritional content, offers a promising solution rooted in Latin American culinary traditions. This study describes the nutritional features of a natural diet based on iron biofortified red beans (BIO102) and examines its physiological impact in newly weaned Balb/C male mice over a 4‐week period. We evaluated weight gain, food intake, fasting blood glucose levels, and physical performance compared to control and regular maize diets. Results indicate that BIO102 and control diets show similar weight gain and food intake, with significant differences noted compared to the regular maize diet. BIO102 diet, characterized by reduced phytic acid content and increased in vitro iron bioaccessibility, significantly lowers fasting blood glucose levels by Week 4. Physical performance measures, encompassing aerobic endurance and limb strength, show no significant differences between BIO102 and control groups. Nutritional analysis highlights BIO102‐based diet's enriched protein content relative to regular maize. This study suggests that BIO102 could offer an alternative to address childhood nutritional deficiencies in Latin America through effective biofortification strategies, serving as a preliminary basis for future clinical investigations.